Spatial and Temporal Evolution of Different‐Scale Ionospheric Irregularities in Central and East Siberia During the 27–28 May 2017 Geomagnetic Storm - V. B. Ovodenko; M. V. Klimenko; I. E. Zakharenkova; A. V. Oinats; D. S. Kotova; A. V. Nikolaev; I. V. Tyutin; D. D. Rogov; K. G. Ratovsky; D. V. Chugunin; P. A. Budnikov; J. C. Coxon; et al. (Space Weather)
Abstract We present a multi‐instrumental study of ionospheric irregularities of different scales (from tens of centimeters to few kilometers) observed over the Central and East Siberia, Russia, during a moderate‐to‐strong geomagnetic storm on 27–28 May 2017. From high‐frequency (HF) and ultrahigh‐frequency (UHF) radar data, we observed an intense auroral backscatter developed right after the initial phase of the geomagnetic storm. Additionally, we examined variations of Global Positioning System (GPS)‐based ROT (rate of TEC changes, where TEC is total electron content) for available GPS receivers in the region. Ionosondes, HF, and UHF radar data exhibited a presence of intense multi‐scale ionospheric irregularities. We revealed a correlation between different‐scale Auroral/Farley‐Buneman ionospheric irregularities of the E layer during the geomagnetic storm. The combined analysis showed that an area of intense irregularities is well connected and located slightly equatorward to field‐aligned currents (FACs) and auroral oval at different stages of the geomagnetic storm. An increase and equatorward displacement of Region 1 (R1)/Region 2 (R2) FACs leads to appearance and equatorward expansion of ionospheric irregularities. During downward (upward) R1 FAC and upward (downward) R2 FAC, the eastward and upward (westward and downward) E × B drift of ionospheric irregularities occurred. Simultaneous disappearance of UHF/HF auroral backscatter and GPS ROT decrease occurred during a prolonged near noon reversal of R1 and R2 FAC directions that accompanied by R1/R2 FAC degradation and disappearance of high‐energy auroral precipitation.